The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pr8121632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Dioxide Nanocomposite Material and Antimicrobial Agents on Mushrooms Shelf-Life Preservation

Abstract: Mushrooms have limited shelf-life and it can be prolonged if suitable conditions and treatments are effectively applied. In this study, nanocomposite material and antimicrobial agents with a combination of chitosan were used as novel packaging material for mushroom preservation. The microbiological analysis, physicochemical properties, headspace gas analysis, and polyphenol oxidase activity (PPO) during cold storage were investigated. As compared with control, coated mushrooms with chitosan (CHS), and nano-tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…These effects were attributed to an internal atmosphere modification that slow some metabolic processes (respiration and transpiration) due to the reduction in the carbon dioxide transmission coefficient (27 g d −1 ) compared to the chitosan-coated fruit (35 g d −1 ). Furthermore, it has been reported a reduced respiration rate effect (oxygen concentration of 5%) in mushrooms coated with a chitosan-titanium dioxide-thymol film, with a decrease in microbial counts (20% of oxygen, yeast, and molds of 4.27 log CFU/g) and polyphenol oxidase activity (17 U/mg protein) after 12 days of storage at 4 • C, compared to those observed in CS-coated (yeast and molds of 6.17 log CFU/g and PPO of 45 U/mg protein) without significant changes in physicochemical parameters such as pH, color attributes, total soluble solids, weight losses, and firmness, which were associated with the inhibition of microbial growth and antioxidant properties of the film, maintaining the mushrooms postharvest quality [67].…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 80%
“…These effects were attributed to an internal atmosphere modification that slow some metabolic processes (respiration and transpiration) due to the reduction in the carbon dioxide transmission coefficient (27 g d −1 ) compared to the chitosan-coated fruit (35 g d −1 ). Furthermore, it has been reported a reduced respiration rate effect (oxygen concentration of 5%) in mushrooms coated with a chitosan-titanium dioxide-thymol film, with a decrease in microbial counts (20% of oxygen, yeast, and molds of 4.27 log CFU/g) and polyphenol oxidase activity (17 U/mg protein) after 12 days of storage at 4 • C, compared to those observed in CS-coated (yeast and molds of 6.17 log CFU/g and PPO of 45 U/mg protein) without significant changes in physicochemical parameters such as pH, color attributes, total soluble solids, weight losses, and firmness, which were associated with the inhibition of microbial growth and antioxidant properties of the film, maintaining the mushrooms postharvest quality [67].…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 80%
“…Eldib 8 , reported that post-harvest change in the hardness loss can be due to the enzymatic degradation of the components which is responsible for the structural rigidity. Nano-material coatings modified the internal gas compositions, reduced the oxygen, and elevated the carbon dioxide concentrations that explained the slower hardness loss of the samples 19 , 20 . Besides, the reduction in respiration rate of coated samples might be responsible for delaying the softening that resulted in the retention of hardness loss during the storage period 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…They have antibacterial activities, and effective film formability 19 . TiO 2 has special morphology, physical–chemical, and mechanical characterizes to expand the shelf-life of numerous food items by dominating the gases influence and harmful rags 20 , 21 . The films can be printed with sodium tripolyphosphate (STP) to act as a crosslinker to stabilize the nanoparticle polymers in the nanoparticle formations 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms contain high protein content, digestible carbohydrates, low fats, vitamins such as B, D, K, A, and C [1]. Mushroom is well-known as therapeutic foods for preventing several diseases such as cancer, hypertension, and hypercholesterolemia in addition to having antitumor, anti-inflammatory, antimicrobial, antioxidant, and immunomodulatory properties [2]. Though, the high perishable nature of mushrooms remains a problem; as mushroom can lose their quality quickly within few days due to occurrences such as physiological injuries, enzymatic browning, off-flavor, loss of firmness of the cap opening, fungal growth owing to senescence, water loss during the storage at commercial temperature due to oxidative reactions.…”
Section: Introductionmentioning
confidence: 99%